Effects of Farm Yard Manure and NPS Fertilizer Rates on Growth and yield of Garlic (Allium sativum L.) at Bale Highlands and mid-altitude, South-Eastern Ethiopia - Gutema, Chala (Pure and Applied Science Advances, 2024)
ABSTRACT Garlic is one of the most important crops worldwide ranking second after onion in order of importance and cultivation. However, the productivity per hectare is low due to poor agronomic practices, lack of improved varieties, diseases and insect pests. Therefore, an on farm experiment was conducted to determine the effect of farm yard manure and NPS fertilizer rates on growth and yield of garlic and to identify economically feasible rates of farm yard manure and NPS fertilizer for garlic production. The treatments are consisted of factorial combinations of four levels of farm yard manure (0, 0.5, 1 and 1.5 tons’ ha-1) and five rates of NPS (0, 50, 100, 150, and 200 kg ha-1) and was laid out as a Randomized complete block designs (RCBD) in three replications. Analysis of variance showed that the plant height was significantly affected by NPS fertilizer while clove length was significantly influence by farm yard manure. On the other hand, the days required to reach 90% physiological maturity, number of leaves per plant, leaf length and number of cloves per bulb were significantly influenced by both FYM and NPS fertilizer. The shortest days (130.8 days) and (131.2 days) to reach days to 90% maturity was observed without application of fertilizers. The maximum plant height (70.50 cm) was recorded from 150 kg NPS ha-1 which statistically at par with 200 and 100 kg NPS ha-1. The highest number leaves per plant (9.23) and (9.65) were obtained from 0.5 tone FYM ha-1 and 150 kg NPS ha-1 fertilizer respectively while the maximum leaf length (48.91) and (48.75) were recorded from 1.5 tones FYM ha-1 and 150 Kg NPS ha-1 respectively. The highest number of cloves per bulb (18.21) and (18.23) were recorded from 1 tone FYM ha-1 and 100 kg NPS ha-1 while the maximum clove length (2.49) was recorded from 0.5 tone FYM ha-1. The interaction effects of FYM and NPS fertilizer were significantly affected bulb weight, clove weight and total bulb yield. The highest bulb weight (30.77g) was obtained from 0.5 tone FYM ha-1 and 150 kg NPS ha-1 while the highest clove weight (2.83 g) was obtained from 0.5 tone FYM ha-1 and 100 kg NPS ha-1. The highest yield (12.91 tone ha-1) was obtained from 0.5 tone FYM ha-1 and 150 Kg NPS ha-1 whereas the minimum yield (9.76 tone ha-1) was obtained from no application of FYM and NPS on garlic. The economic analysis also revealed that the highest net return of (2316300 ETB ha-1) with marginal rate of return (308.84%) was obtained at application of 0.5 tone FYM ha-1 and 150 Kg NPS ha-1. Therefore, based on the results of the yield, growth, yield parameters and economic analysis use of 0.5 tone FYM ha-1 and 150 Kg NPS ha-1. can be tentatively recommended for farmers for production of garlic in the study area. Keywords: garlic, NPS, cloves, FYM, bulb yield